Effects of arginine modified additives on humic acid formation and microbial metabolic functions in biogas residue composting. Issue 6 (December 2022) - Lu, Mingyi; Feng, Quan; Li, Xu; Xu, Baochao; Shi, Xiaoshuang; Guo, Rongbo
Abstract: The complex linked fibrous structure of biogas residue (BR) maximally hinders degradation, and strategies are needed to improve the efficiency of BR composting. Oyster shell is a kind of reusable resource, which can be used as a composting additive. This study aimed to achieve highly humification of lignocellulosic compost by adding arginine-modified oyster shells. The modified oyster shell powder prepared by acid etching and ultrasonic was added to straw biogas residue composting. Results showed that the addition of modified oyster shell enhanced the lignocellulose degradation, especially the degradation ratio of lignin reached 44.16% at the end of composting. The utilization of amino acids and reducing sugars was improved with a reduction of 80.44% and 37.53% respectively, and the humic acid content reached 1.32 times that of the control group. This was because more intermediates were involved in carbon sequestration rather than oxidized to carbon dioxide, in line with the carbon dioxide emission results. In addition, the sequence abundance changes in tricarboxylic acid cycle, oxidative phosphorylation and carbon fixation also contributed to the high humification. High throughput sequencing results showed that addition of modified oyster shell increased the bacterial diversity and abundance, including Firmicutes and Chloroflexi, which were positively correlated with lignin degradation. Graphical Abstract: ga1 Highlights: A new arginine modified oyster shell was developed as composting additive. The addition of Arg-OSP increased the humification index. The utilisation of amino acids and sugars was improved with Arg-OSP added. Additives affect the composition of bacterial community in the later stage. The potential metabolic functions of bacterial communities were identified.